Diagnosis of breast lump by fine needle aspiration cytology and mammography. - Rahman, MZ; Sikder, AM; Nabi, SR (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):658-64 The abstract of this article is available on the PubMed website